Effect of Seasonality on Chemical Composition and Antibacterial and Anticandida Activities of Argentine Propolis. Design of a Topical Formulation - Isla, María Inés; Dantur, Yanina; Salas, Ana Lilia; Danert, Fátima Carolina; Zampini, Iris Catiana; Arias, Myriam; Ordóñez, Roxana Mabel; Maldonado, Luis Maria; Bedascarrasbure, Enrique Luciano; Nieva Moreno, María Inés (Sage Publishing, 2022)
The effect of seasonality on Argentine propolis collected during one year on its phenolic and flavonoid content and on the growth of Gram-positive and Gram-negative antibiotic resistant bacteria and Candida species was evaluated. Extracts of propolis samples collected in the summer and spring showed higher phenolic and flavonoid contents than the samples collected in other seasons (5.86 to 6.06 mg GAE/mL and 3.77 to 4.23 mg QE/mL, respectively). The propolis collected in summer and autumn showed higher antibacterial activity (30 μg/mL) than the other samples (MIC values between 30 and 120 μg/mL). No antibacterial activity was detected against Gram-negative bacteria. Also, these extracts were able to inhibit the development of five Candida species, with MFC values of 15-120 μg/mL. Pharmaceutical formulations containing the more active propolis extract were prepared. The hydrogel of acrylic acid polymer containing summer propolis extract as an antimicrobial agent showed microbiological, physical and functional stability during storage for 180 days. The pharmaceutical preparation, as well as the propolis extracts, was active against Candida sp. and antibiotic-multi-resistant Gram-positive bacteria. These results reveal that propolis samples collected by scraping in four seasons, especially in summer in Calingasta, San Juan, Argentina, can be used to obtain tinctures and hydrogels with antibacterial and antimycotic potential for topical use.